LPTO-10. ASSESSMENT OF LEPTOMENINGEAL CARCINOMATOSIS DIAGNOSIS AND OUTCOMES FROM 2005 TO 2015 AT THE OHIO STATE UNIVERSITY. (12th August 2019) - Williams, Nicole; Rinehardt, Hannah; Morgan, Evan; Kassem, Mahmoud; Palettas, Marilly; Puduvalli, Vinay; Giglo, Pierre; Lustberg, Maryam; Wesolowski, Robert; Sardesai, Sagar; Stover, Daniel; Vandeusen, Jeffrey; et al.
Abstract: BACKGROUND: Leptomeningeal carcinomatosis (LMC) is a complication of solid tumor malignancies where tumors metastasize to the leptomeninges. LMC complicates 4–15% of malignancies with incidence increasing as survival of patients with advanced cancer improves. Diagnostic methods include magnetic resonance imaging (MRI) and cerebrospinal fluid (CSF) cytology. We assessed detection methods, incidence, and outcomes of LMC at The Ohio State University Comprehensive Cancer Center from 2005–2015. METHODS: This was a single-institution retrospective study of 160 patients with confirmed diagnosis of LMC. Patients with hematologic and central nervous system malignancies were excluded. Descriptive statistics were used to summarize demographic and clinical characteristics. Overall survival (OS) was defined as time from LMC diagnosis to death or last known follow-up, and was generated using Kaplan-Meier methods. RESULTS: Median age of LMC diagnosis was 55.8 years (range: 48, 62.5). 69 (43%) patients had primary breast cancer, 41 (26%) had lung cancer, and 17 (11%) had melanoma. 73 patients (46%) presented with stage IV disease at initial diagnosis of the primary cancer, 41 (26%) with stage III disease, and 26 (16%) with stage II disease. Median time from diagnosis of primary cancer to diagnosis of LMC was 2 years (range: 0, 31.2). 158 (99%) patients had metastases at the time of LMC diagnosis, predominantly in bone (36%) or brain (36%). Median OS was 1.9 months (CI: 1.3, 2.5). 160 (100%) patients had an MRI of the brain or spine and 155 (97%) had MRI findings consistent with LMC. 75 (47%) patients underwent lumbar puncture, and 39 (52%) had CSF cytology positive for malignancy. CONCLUSIONS: Despite treatment, prognosis remains poor and confirmation of diagnosis can be challenging. This study highlights the need for novel therapeutics and improved diagnostic techniques for patients with LMC.